2021
DOI: 10.3389/fnbeh.2020.616389
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Isolation Stress and Unpredictable Chronic Mild Stress for the Establishment of Mouse Models of Depressive Disorder

Abstract: This study aimed to help to understand the influence of stress on depression, which reflects the social environments of especially solitary life and the increasing prevalence of depressive disorders. To determine the distinguishable features of two-representative animal models of stress-induced depressive disorder, we compared isolation stress (IS) and unpredictable chronic mild stress (UCMS). After 4-week of stress, both models showed significant depressive- and anxiety-like behaviors in an open field test (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…The current study did note a generalized hyperactivity in the open‐field arena in CRS‐exposed mice, which is supported by similar studies utilizing mild stressors 91,96 . Despite this, entries into the center square, which is associated with exploratory behavior, were unaltered by CRS in either dietary group, which contrasts our previous work and others using restraint and social isolation stressors 24,97,98 . In our previous work, we demonstrated that after 9 weeks of feeding, a 3‐week CRS intervention (30min per day) induced synergistic effects on cardiometabolic parameters resulting in elevated insulin levels and worsened myocardial tolerance to ischemic/reperfusion injury.…”
Section: Discussionsupporting
confidence: 82%
“…The current study did note a generalized hyperactivity in the open‐field arena in CRS‐exposed mice, which is supported by similar studies utilizing mild stressors 91,96 . Despite this, entries into the center square, which is associated with exploratory behavior, were unaltered by CRS in either dietary group, which contrasts our previous work and others using restraint and social isolation stressors 24,97,98 . In our previous work, we demonstrated that after 9 weeks of feeding, a 3‐week CRS intervention (30min per day) induced synergistic effects on cardiometabolic parameters resulting in elevated insulin levels and worsened myocardial tolerance to ischemic/reperfusion injury.…”
Section: Discussionsupporting
confidence: 82%
“…Such G x E interactions seen in these behaviors may suggest that environmental factors (adolescent social isolation) influence similar regions/ pathways of the brain as genetic risk factors (Kpna1 deletion), where the cumulative effects from both factors cause increased levels of impairment. Administration of social isolation stress has been shown to alter performance in FS along with increases in serum corticosterone levels and hippocampal microglial activation [66]. Similar increases in serum corticosterone levels have been found in mice with decreased IA performance after social isolation [67].…”
Section: Discussionmentioning
confidence: 58%
“…The first is restraint stress in which a mouse is placed in a 50 mL conical tube for several hours at a time for several days in a row [80,108]. The second is the chronic unpredictable model of stress (CUMS) in which animals are subjected to several different stressors, including wet bedding, sleep deprivation, foot-shock, cage tilting, water and food deprivation, confinement, continuous illumination, cold stress, and/or forced swim on a random basis [99,109,110]. The CUMS model is thought to be representative of the stressors faced by humans in everyday life and is often used in depression models to study the therapeutic efficacy of candidate anti-depressants; however, a recent study comparing the CUMS to IS found that social isolation is a stronger inducer of depression-like behavior and is more relevant to the role of isolation in stress-induced depression in people [110].…”
Section: Purposeful Imposition Of Experimental Stress For Researchmentioning
confidence: 99%
“…The second is the chronic unpredictable model of stress (CUMS) in which animals are subjected to several different stressors, including wet bedding, sleep deprivation, foot-shock, cage tilting, water and food deprivation, confinement, continuous illumination, cold stress, and/or forced swim on a random basis [99,109,110]. The CUMS model is thought to be representative of the stressors faced by humans in everyday life and is often used in depression models to study the therapeutic efficacy of candidate anti-depressants; however, a recent study comparing the CUMS to IS found that social isolation is a stronger inducer of depression-like behavior and is more relevant to the role of isolation in stress-induced depression in people [110]. Other models have been developed based on inducing fear, but are not widely used, including exposure of mice to recordings of mice screaming [111], housing adjacent to cats [112], predator odors [113], or chronic social defeat stress (CSDS) in which stranger/aggressor mice are introduced into the cage [101,114].…”
Section: Purposeful Imposition Of Experimental Stress For Researchmentioning
confidence: 99%
See 1 more Smart Citation